Application of a functionalized ionic liquid extractant tributylmethylammonium dibutyldiglycolamate ([A336][BDGA]) in light rare earth extraction and separation - Qiu, Lina (PLoS One, 2018)
A type of functionalized ionic liquid extractant, tributylmethylammonium dibutyldiglycolamate ([A336][BDGA]), was synthesized, and its extraction ability of light rare earth elements, namely, La(III), Ce(III), Pr(III) and Nd(III), wascompared with that of other functionalized ionic liquid extractants, including tributylmethylammonium dioctyldiglycolamate and diglycolic amide extractants N,N,N,N-tetrabutyl-3-oxapentane-diamide (TBDGA) and N,N,N,N-tetraoctyl-3-oxapentane-diamide (TODGA). The study of extraction behavior indicated that the ionic liquids exhibited better extraction properties than the amides under lower acidity conditions. The effects of the pH and concentration of the extractant on the extraction behavior of [A336][BDGA] on light rare earths were determined. A separation strategy of mixed light rare earths was investigated by means of extraction chromatography using [A336][BDGA] as the stationary phase. As a result, nearly pure La(III), Ce(III), Pr(III) and Nd(III) were obtained, respectively. A new strategy of separating mixed light rare earths was established by means of extraction chromatography. The stationary phase of [A336][BDGA] was used in this strategy. The four rare earths elements, La(III), Ce(III), Pr(III) and Nd(III), achieved baseline separation.